A Livšic Type Theorem for Germs of Analytic Diffeomorphisms - Navas-Flores, A (2013)
We deal with the problem of the validity of the Livšic theorem for cocycles of diffeomorphisms over a hyperbolic dynamics that satisfy the periodic orbit condition. We give a result in the positive direction for cocycles of germs of analytic diffeomorphisms at the origin. © 2013 IOP Publishing Ltd & London Mathematical Society.